Non‐invasive assessment of fibrosis regression and portal hypertension in patients with advanced chronic hepatitis C virus (HCV)‐associated liver disease and sustained virologic response (SVR): 3 years follow‐up of a prospective longitudinal study. Issue 11 (1st October 2021) - Knop, Viola; Hoppe, Daniel; Vermehren, Johannes; Troetschler, Sven; Herrmann, Eva; Vermehren, Annika; Friedrich‐Rust, Mireen; Sarrazin, Christoph; Trebicka, Jonel; Zeuzem, Stefan; Welker, Martin‐Walter
Abstract: Long‐term effects on cirrhosis and portal hypertension of direct antiviral agent (DAA)‐based eradication of hepatitis C virus (HCV) are still under debate. We analysed dynamics of liver and spleen elastography to assess potential regression of cirrhosis and portal hypertension 3 years post‐treatment. Fifty‐four patients with HCV‐associated cirrhosis and DAA‐induced SVR were included. Liver and spleen stiffness were measured at baseline (BL), end of treatment (EOT), 24 weeks after EOT (FU24) and 1, 2 and 3 (FU144) years post‐treatment by transient liver elastography (L‐TE) and point shear wave elastography (pSWE) using acoustic radiation force impulse (ARFI) of the liver (L‐ARFI) and spleen (S‐ARFI). Biochemical, virological and clinical data were also obtained. Liver stiffness assessed by L‐TE decreased between BL [median (range), 32.5(9.1–75) kPa] and EOT [21.3(6.7–73.5) kPa; p  < .0001] and EOT and FU144 [16(4.1–75) kPa; p  = .006]. L‐ARFI values improved between EOT [2.5(1.2–4.1) m/s] and FU144 [1.7(0.9–4.1) m/s; p  = .001], while spleen stiffness remained unchanged. Overall, L‐TE improved in 38 of 54 (70.4%) patients at EOT and 29 of 38 (76.3%) declined further until FU144, whereas L‐ARFI values decreased in 30/54 (55.6%) patients at EOT and continued to decrease in 28/30 (93.3%) patients at FU144. Low bilirubin and high albumin levels at BL were associated with improved L‐ARFI values ( p  = .048) at EOT or regression of cirrhosis (<12.5 kPa) by L‐TE at FU144 ( p  = .005), respectively. Liver stiffness, but not spleen stiffness, continued to decline in a considerable proportion of patients with advanced liver disease after HCV eradication.